An unusual two-stage infection following a scolopendra bite - Puzzo, Agnese; Pari, Carlotta; Bettinelli, Giulia; Raggini, Filippo; Paderni, Stefania; Belluati, Alberto (Acta Biomedica Atenei Parmensis, 2020)
Background:  Scolopendrae represent the best-known genus of centipedes. They are nocturnal general feeders with strong mandibles and venomous fangs which leave visible puncture marks at the bite site. The bite accidents occur during the warm rainy season and mostly take place on the extremities. Following the bite, the most common symptoms are mild: limited localized erythema, pain, swelling, local itching and burning sensation. However, more severe local and systemic sequelae can not be excluded. Method: we report the case of a 63-year-old man with fever and a widespread edema of the right hand and forearm, happened as a consequence of a Scolopendra Subspinipes bite. During the weeks following the bite, he developed a severe unusual superinfection via hematogenous dissemination, which  required a double surgical debridement and a targeted intravenous antibiotic therapy. Results: the complete clinical recovery took over two month. Conclusions: Many victims of Scolopendra envenomation do not seek medical attention since most symptoms will resolve spontaneously. The case presented falls within the spectrum of those rare cases which escalate due to bacterial superinfection.